ANTANAS MACEINA’S CONCEPT OF PUPIL’S ACTIVITY IN TERMS OF PERSONALITY SELFCREATION - Tijūnėlienė, Ona; Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 2008)
Educational goals have always been directed towards the development of personality. A. Maceina considers the development of pupil’s activity as an important educational goal. Today it is universally agreed that a person’s activity paves the way to a holistic personality. The aim of this article is to show A. Maceina’s concept of pupil’s activity as an essential factor of personality’s self-creation. The article is based on the concept of the man as an active creature who is able to pursue self-development. The first part of the article gives A. Maceina’s conception of pupil’s activity. The comparison and analysis of traditional and labour schools provides the understanding of A. Maceina’s activity concept. A. Maceina describes activity through the prism of two contradictory words: active – passive. A. Maceina states that the pupil is neither active, nor passive. He is receptive. Further, the elements of receptiveness are introduced. Also C. R. Roger’s theoretical aspects of creativity are located and compared with A. Maceina’s conception of pupil’s activity. The second part of the article addresses the issue of pupil’s activity in education. It takes up and discusses A. Maceina’s idea that a pupil is not only an object but also a subject in education. In his opinijon it is impossible to mechanically form a person and hold an idea that a man’s spirit seeks to act being attempted by an eternal law of self-creation, which is a characteristic feature of the man. This part of the article also involves A. Maceina’s description of the nature of the man’s activity during different age periods.